Impact of Perceived Peer Attitudes and Social Network Diversity on Violent Extremist Intentions - Kaczkowski, Wojciech (Terrorism and political violence, 2022)
Perceived peer attitudes (PPA) often influence young men’s violent attitudes and behaviors, although people with higher social network diversity (SND) are less likely to adopt their close peers’ attitudes. There is currently limited research examining this role of peer networks in the development of violent extremism (VE). Consequently, the current study sought to answer the following questions: (1) How are PPA, personal attitudes, and VE intentions related to each other? (2) Does the relationship between PPA and VE intentions differ based on SND? The study sample consisted of 340 men (eighteen to twenty-nine years old) recruited via Amazon MTurk. Participants first indicated their most salient social group and listed their five closest male peers. Next, they reported their VE attitudes, intentions, and their peers’ attitudes. Overall, PPA were positively associated with VE intentions through the partial mediating effect of personal attitudes. SND moderated the relationship between PPA and VE attitudes: participants with more diverse networks were less likely to hold beliefs similar to their PPA. The study highlights the potential role of SND as a protective factor against the harmful effects of PPA. Notably, it underscores the need for social-ecological approaches to counter VE, offering community involvement and growth of social ties.